Conceptualizations of Romantic Relationship Commitment Among Low-Income African American Adolescents - Barton, Allen W. (2017)
Few studies have examined adolescents’ understanding of romantic relationship commitment, particularly among African American youth. Using three waves of semistructured interviews, the present descriptive study addresses this topic by exploring the ways in which 20 African American adolescents (age range 13-19 years) from low-income backgrounds conceptualize and describe commitment in romantic relationships. Qualitative analyses revealed three main themes related to defining commitment, indicating that which commitment provides, and describing the nature of commitment in different relationship contexts. Findings inform psychological research and practice relating to commitment and romantic relationships among African American adolescents